Science communication in the digital age: Trends, gaps, and interdisciplinary opportunities - Phogat, Peeyush; Rab, Shanay; Wan, Meher (Information services & use, 2025)
This manuscript reviews the evolution of science communication research over the past 2 decades, highlighting publication trends and citation patterns. Key areas include public engagement, media influence, and digital tools. The study shows a rise in both the volume and impact of literature, especially after global events like the COVID-19 pandemic. However, it identifies gaps in research on digital tools and outreach strategies, particularly in non-Western contexts. This work aims to improve public understanding and foster informed engagement with scientific issues.